Pemanfaatan Tanaman Obat Keluarga Dalam Meningkatkan Imun Keluarga Ibu-ibu PKK - Misrita, Misrita; Jaya, Hery Palangka; Ludang, Yetrie; Qalyubi, Imam; Noriman, Noriman (Jurnal Pengabdian Kampus, 2023)
It is possible to defeat the Covid-19 virus by boosting the body's defenses. Using family medicinal plants, which typically grow more naturally in yards and are widely used as food additives as well as for healing, disease prevention, improving immunity, and restoring freshness, which ultimately benefits public health, is one of the ways to boost immunity. The community still has a limited understanding of and reaction to the usage of therapeutic herbs. It is judged important to perform community service in relation to the administration of the family's medicinal plants after observing the response of a group of women in Talio Village who have family medicinal plants. The strategy employs community empowerment techniques, particularly for the target population through counseling and training.  In particular, the target group receives counseling and training while producing a healthy butterfly pea flower drink for ten women and cadres in Talio Village as part of the approach method's utilization of community empowerment techniques. The outcomes of this activity demonstrate that mothers and health professionals in Talio Village now have a more comprehensive understanding of how to prepare a healthy butterfly pea flower beverage as a consequence of counseling and training utilizing training materials. The answer score, where the mean post-test score is 86.20 and greater than the pre-test score of 72.3, serves as proof of this. Knowledge growth as a percentage grew by 14.17%. The outcomes of community service through counseling and education by offering instruction on how to make healthy butterfly pea flower beverages help boost moms' and staff members' understanding of how to strengthen the immune system of the family. PKK Desa is advised to organize a small group of traditional herbal medicine firms and host a village-wide competition for family medicinal plants.